Buruknya Kualitas Perkawinan Pemicu Kekerasan Seksual: Studi terhadap Pelaku Kekerasan Seksual Anak di Kabupaten Agam - Ashabul Fadhli (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The stalled needs of fulfilling sexual needs for some man who divorced or death divorced with their wives have been believed to be one of the causes of child sex perpetrator to carry out their actions. For men who have a particular social background, the desire tocommit a crime is likely to have a higher chance. This assumption begins with the tendency of men as husbands who are more eager to fulfill their sexual needs that may end positive or negative. But when a man no longer has a place tofulfill his desire, they will divert the purpose of his power to another subject that is considered vulnerable and easy to master. Starting from field research, this research has succeeded to deepen the testimony of three child sex perpetrators who are all domiciled in Agam regency of West Sumatra. The result of exploring the three perpetrators, there are indicators that are interconnected with each other about how they approach the child. Sense of power as an adult male by giving a caring attitude, a sense of security and friendship is aimed to form a circle of power that easily weaken, control and then will attack the child.